Optimization of Waqf Management in Increasing Public Trust in Nazhir - Rizki Nurhidayat; Laila Masruro Pimada; Habiburrahman Habiburrahman; Cindy Putri Hariyatin (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2022)
Indonesia has the potential for waqf to be able to grow and develop better. However, this potential is not accompanied by good management. This study aims to increase public trust in nazhir by optimizing waqf management. The method used is a literature study method. In identifying research problems using SWOT analysis. This analysis will show the related strengths, weaknesses, opportunities, and threats in waqf management in Indonesia. In terms of strength, the majority of the Indonesian population is Muslim, there are laws and WCP, as well as various waqf instruments. While the aspects of weakness include the lack of transparency of nazhir, the management of waqf is not yet professional, and the promotion and development of waqf is not optimal. There are also opportunities in waqf management which includes a large potential for cash waqf. In terms of threats, it consists of a lack of public understanding, the emergence of moral hazard nazhir waqf, and the presence of other social investments. So the results of this study will provide several strategies in overcoming the problems of waqf management. Such as by improving the management of waqf management, increasing nazhir certification, and increasing the promotion and marketing of waqf.